Ethanol-derived acetaldehyde: pleasure and pain of alcohol mechanism of action - Muggironi, Giulia; Fois, Giulia R.; Diana, Marco (Frontiers in Behavioral Neuroscience, 2013)
Acetaldehyde (ACD), the first metabolite of ethanol (EtOH), has been implicated in several actions of alcohol, including its reinforcing effects. Previously considered an aversive compound, ACD was useful in alcoholic’s pharmacological treatment aimed at discouraging alcohol drinking. However, it has recently been shown that EtOH-derived ACD is necessary for EtOH-induced place preference and self-administration, thereby suggesting a possible involvement of ACD in EtOH motivational properties. In addition, EtOH-stimulating properties on DA neurons are pre-vented by pharmacological blockade of local catalase H2O2 system, the main metabolic step for bio-transformation of EtOH into ACD within the central nervous system. It was further shown that pretreatment with thiol compounds, like L-Cysteine or D-Penicillamine, reduced EtOH and ACD-induced motivational effects, in fact preventing self-administration of both EtOH and ACD, thus suggesting a possible role for ACD as a bio-marker useful in evaluating potential innovative treatments of alcohol abuse. These findings suggest a key role of ACD in the EtOH reinforcing effects. In the present paper we review the role of EtOH-derived ACD in the reinforcing effects of EtOH and the possibility that ACD may serve as a therapeutically targetable biomarker in the search for novel treatments in alcohol abuse and alcoholism.